MANAGEMENT OF “SIGAP-ANESTHESI”: SYNERGY OF AMPLE EDUCATION AND BASIC LIFE SUPPORT TO ENHANCE PRE-ANESTHESIA PREPAREDNESS OF HYPERTENSIVE PATIENTS’ FAMILIES IN THE CENTRAL SURGICAL INSTALLATION WAITING AREA OF BANGLI REGIONAL GENERAL HOSPITAL - Ni Putu Yusniawati, Yustina; Shuarsedana Putra, I Gde Agus; Ileatan Lewar, Emanuel; Sri Rahayuni, Ni Wayan; Angelina Djami, Rani Valentina; Juniawan, Putu Denny; Carisa Meikayani, Ida Ayu; Feri Irawan, I Kadek (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
Hypertension is a chronic condition that often remains asymptomatic but is associated with a high risk of perioperative complications. In adults, hypertension is classified as essential or secondary, while in pregnancy it presents as gestational hypertension or preeclampsia, which may progress to HELLP syndrome. Patients with hypertension undergoing surgical procedures are at increased risk of complications, including stroke, arrhythmias, and mortality, particularly when blood pressure is poorly controlled. Certain anesthetic agents, such as sevoflurane and propofol, may induce significant hypotension, highlighting the importance of comprehensive pre-anesthetic assessment. The AMPLE approach (Allergy, Medication, Past Medical History, Last Meal, Environment/Event) serves as a systematic method to identify perioperative risks and support safe anesthesia planning.Preliminary observations at Bangli Regional Hospital reported 20–30 surgical cases with comorbid hypertension per month, including 10–20 cases of gestational hypertension. To address this issue, a community service program was conducted to provide education on pre-anesthetic assessment using AMPLE and Basic Life Support (BLS) training for patients’ families. The program was positively received, with participants demonstrating appropriate BLS techniques and actively engaging during counseling sessions. These findings suggest that routine implementation of AMPLE education and BLS training may enhance family preparedness and patient safety in perioperative and emergency situations.